Carbohidrates contents in stem of some pineapple cultivars - Carvalho, Vânia Déa de; Cunha, Getúlio Augusto Pinto da; Paula, Miralda Bueno de; Chitarra, Maria Isabel Femandes (Pesquisa Agropecuaria Brasileira, 2014)
The following variables were determined: stem weight, dry matter, starch, total, reducing and nonreducing sugars and celulose on stem of seventeen pineapple cultivars. The present study aims at selecting the best pineapple varieties for industrial proposes. Smooth Cayenne Liso and Smooth Cayenne Espinhoso varieties presented stem with high starch contents, therefore it can be used for alcohol ethylic production. The pineapple stem starch contents were higher than sugars and cellulose contents. All of the varieties presented stem with reducing sugars contents higher than nonreducing sugars contents, except Huitota, Ananás Tricolor and Pico de Rosa varieties, in which nonreducing sugars contents were the highest.